A method for improving the tensile properties of powder metallurgy iron-based parts
Patent Information
- Application Number
- CN202510441872.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-04-09
AI Technical Summary
[0004]而中国专利CN109487314A公开了一种提高钢铁表面耐磨性能的渗硼方法,该方法通过钢铁表面的预处理、电解溶液的配制和渗硼处理来解决;所得到的渗硼层主要由单一Fe2B相组成,需要在添加剂和电解溶液的配制条件下制备,所制备渗硼层的厚度较薄,脆性较大,拉伸性能较差
[0025]上述方案,本发明提出了一种粉末冶金铁基零件提升拉伸性能的制备方法,能够解决现有技术中存在的技术问题,例如粉末冶金铁基零件只注重于添加硼元素来提高表面的硬度,从而提高耐磨性能,并未关注Fe2B单相组织的生成以及拉伸性能的提高,且所制备的表面渗硼层不是太薄就是组织分布不均匀,并未进行组织的扩散,有的只是在材料表面制备一层涂层,并不能够提高零件的整体拉伸性能。
Smart Images

Figure CN120460733B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of powder metallurgy preparation of low alloys, and in particular to a method for improving the tensile properties of powder metallurgy iron-based parts. Background Technology
[0002] Powder metallurgy is a process that uses metal powders as raw materials to prepare mechanical parts through processes such as powder mixing, pressing, and sintering. It boasts advantages such as high efficiency, low consumption, high material utilization, and uniform material structure, and is widely used in aerospace, automotive, and other industrial fields. However, the tensile properties of powder metallurgy materials are severely limited by problems such as porosity and surface roughness. Fatigue failure of powder metallurgy materials is a major problem in engineering applications; therefore, improving the fatigue behavior of powder metallurgy materials is an important task in this field.
[0003] Boronizing treatment can achieve a surface structure with high hardness and good resistance to high-temperature oxidation and corrosion. However, since boronizing generally results in a double-layer structure of FeB and Fe2B, the FeB layer is relatively brittle. Only a single-phase Fe2B layer can achieve good toughness. After boronizing and cooling, the combined effects of high thermal stress and phase transformation stress often lead to transverse cracks in the boronized layer. Furthermore, the significant porosity on the surface of the boronized layer severely affects surface hardness, negatively impacting its practical engineering applications. Ideally, boronizing should produce a dense, fine-grained, and porous single-phase Fe2B layer.
[0004] Chinese patent CN109487314A discloses a boronizing method to improve the wear resistance of steel surfaces. This method involves pretreatment of the steel surface, preparation of an electrolytic solution, and boronizing treatment. The resulting boronized layer is mainly composed of a single Fe2B phase and needs to be prepared under the conditions of additives and electrolytic solution preparation. The prepared boronized layer is relatively thin, brittle, and has poor tensile properties.
[0005] Chinese patent CN108796426A discloses a boronizing superhardening process for metal surfaces. This method involves quenching, cleaning, tempering, boiling in water for 2-3 days, and TD treatment after boronizing to obtain the product. However, the process is complex, difficult to operate, and has low production efficiency. While the resulting product has very high hardness, its tensile properties are not effectively improved.
[0006] Chinese patent CN113481503A discloses a method for preparing boron particle-reinforced metal matrix composites, the composite material and its application. The method uses resonant ball milling to prepare uniformly mixed boron-metal micron powder, and then uses supersonic low-pressure cold spraying to spray a composite coating on the metal substrate in an additive manufacturing manner to produce a composite material. Obviously, the preparation process is costly and inefficient, does not form FeB and Fe2B structures, and does not undergo heat treatment to improve tensile properties. Summary of the Invention
[0007] To address the technical problems existing in current technologies, such as the fact that powder metallurgy iron-based parts only focus on adding boron to increase surface hardness and thus improve wear resistance, without considering the formation of Fe2B single-phase structure and the improvement of tensile properties, and that the prepared surface boron-infiltrated layer is either too thin or has an uneven microstructure distribution without diffusion, sometimes merely forming a coating on the material surface and failing to improve the overall tensile properties of the part, this invention proposes a method for preparing powder metallurgy iron-based parts that improves tensile properties and solves the aforementioned problems. The technical solution is as follows:
[0008] A method for preparing powder metallurgy iron-based parts with improved tensile properties, comprising the following steps:
[0009] S1. Sample processing: Clean the oil stains on the surface of the powder metallurgy iron-based parts sample, and grind and polish the sample surface to obtain a smooth iron-based parts sample.
[0010] S2, Initial powder coating of sample surface: B powder is applied to the smooth iron-based part sample surface of S1, and tantalum foil is used to wrap and compact it to obtain iron-based part sample coated with B powder.
[0011] S3. Preparation of boron-impregnated layer on sample surface: The iron-based part sample coated with B powder in S2 is placed in a tube furnace, hydrogen gas is introduced to prevent oxidation, and the sample is heated and kept at a constant temperature to obtain an iron-based part sample with a boron-impregnated layer on the surface.
[0012] S4. Diffusion treatment of samples: The iron-based parts sample with surface boronizing layer in S3 is cleaned to remove the remaining boron powder, and then subjected to diffusion heat treatment, followed by air cooling to room temperature to obtain powder metallurgy iron-based parts with improved tensile properties.
[0013] Optionally, the alloy composition of the powder metallurgy iron-based parts sample in S1 is C≤0.81wt.%, Cu≤2.07wt.%, Ni≤2.44wt.%, Mo≤0.53wt.%, Mn≤0.17wt.%, P≤0.45wt.%, with the remainder being Fe.
[0014] Optionally, the surface roughness Ra of the smooth iron-based part sample in S1 is 0.8-2 μm.
[0015] Optionally, the B powder in S2 is 1-3μm industrial B powder, which completely coats the powder metallurgy parts. The B powder thickness is about 3-5mm, the tantalum foil thickness is 0.10±0.05mm, and the pressure is 200MPa.
[0016] Optionally, the heating rate in S3 is 5-10℃ / min, the temperature is 850-950℃, the holding time is 4-8h, and the thickness of the boronized layer on the surface is 30-160μm.
[0017] Optionally, the surface hardness of the iron-based part samples with a surface boronizing layer in S3 is 1440-1600 HV. 0.5 The surface porosity is 5%-20%, the surface roughness is 0.8-3.0μm, the yield strength is 265-300MPa, the tensile strength is 265-380MPa, the elongation is 2.3-4.5%, and the strength-ductility product is 0.61-1.71GPa·.
[0018] Optionally, in the surface boronized layer of the iron-based part sample with surface boronized layer in S3, the Fe2B is distributed in a serrated shape, with a thickness of about 15-60 μm, distributed in the subsurface layer, and grows closely with the substrate.
[0019] Optionally, the heating rate of the diffusion heat treatment in S4 is 5℃ / min, the temperature is 950-1000℃, the holding time is 2-4h, and the thickness of the boronized layer on the surface is 60-95μm.
[0020] Optionally, the surface hardness of the powder metallurgy iron-based parts in S4 that improve tensile properties is 1182-1230 HV. 0.5 The surface porosity is 5%-10%, the surface roughness is 0.8-2.0μm, the yield strength is 100-130.3MPa, the tensile strength is 150-220.9MPa, the yield-to-tensile ratio is 0.452-0.869, the elongation is 7.8-12.4%, and the strength-ductility product is 1.17-2.74GPa·s.
[0021] Optionally, in the boronized layer on the surface of the powder metallurgy iron-based parts in S4 that improves tensile properties, the Fe2B has a serrated shape, a thickness of about 40-70 μm, and is distributed relatively uniformly on the surface.
[0022] Technical principle of the invention:
[0023] This invention first coats the sample surface with boron powder. Through high-temperature heating, the boron powder melts and penetrates deep into the sample surface, diffusing at grain boundaries and defects. In the initial stage of borination, boron atoms penetrate the steel surface at high temperature, reacting with iron to form two borides: FeB and Fe2B. Due to the boron concentration gradient, the surface is FeB, and the subsurface is Fe2B. Then, through further diffusion annealing, boron atoms diffuse from the high-concentration region (FeB) to the low-concentration region (Fe2B and the matrix), reducing the boron concentration in FeB and causing it to gradually transform into Fe2B, eventually becoming entirely Fe2B. After complete transformation to Fe2B, the material surface exhibits high hardness and good toughness, while avoiding the brittleness of FeB, significantly improving wear resistance and tensile properties.
[0024] The above technical solution has at least the following advantages compared with the existing technology:
[0025] The above-mentioned solution, proposed by the present invention, is a method for improving the tensile properties of powder metallurgy iron-based parts. It can solve the technical problems existing in the prior art. For example, powder metallurgy iron-based parts only focus on adding boron to improve the surface hardness and thus improve wear resistance, without paying attention to the formation of Fe2B single-phase structure and the improvement of tensile properties. Moreover, the prepared surface boron-diffused layer is either too thin or the structure is unevenly distributed, without the diffusion of the structure. Some are just a coating layer prepared on the material surface, which cannot improve the overall tensile properties of the parts.
[0026] The preparation method of this invention is simple, uses only B powder as raw material instead of composite slurry, has low production cost, and the thickness of the diffusion layer can be adjusted according to the heat preservation time and temperature, which can significantly improve the density and room temperature mechanical properties of powder metallurgy materials, and is easy to promote to other metal material fields.
[0027] This invention achieves uniform coating of B-powder on the sample surface through initial powder coating, effectively avoiding the problem of uneven infiltration layer.
[0028] This invention prepares a boron-impregnated layer on the sample surface, resulting in a FeB+Fe2B double-layer boron-impregnated layer, which significantly improves yield strength, tensile strength, surface hardness, and wear resistance.
[0029] This invention improves the density of powder metallurgy materials through sample diffusion treatment, increases the proportion of Fe2B, improves plasticity, and enhances overall performance.
[0030] The surface hardness of the powder metallurgy iron-based parts with improved tensile properties prepared by this invention is 1182-1230 HV. 0.5The surface porosity is 5%-10%, the surface roughness is 0.8-2.0μm, the yield strength is 100-130.3MPa, the tensile strength is 150-220.9MPa, the yield-to-tensile ratio is 0.452-0.869, the elongation is 7.8-12.4%, and the strength-ductility product is 1.17-2.74GPa·s.
[0031] In summary, compared with other traditional methods, the method of this invention can obtain a single-layer, dense Fe2B diffusion layer with a thickness of 60-95μm in powder metallurgy low alloy steel through boronizing and diffusion heat treatment. The surface layer has few pores and no subsequent grinding processing is required, which can greatly improve hardness, strength and elongation. The method is simple to operate, environmentally friendly, low in cost, short in process and high in efficiency, which is conducive to large-scale industrial production and promotion. Attached Figure Description
[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0033] Figure 1 This is a cross-sectional SEM image of the diffusion layer without diffusion heat treatment in a method for improving the tensile properties of powder metallurgy iron-based parts according to Embodiment 1 of the present invention.
[0034] Figure 2 This is a cross-sectional SEM image of the powder metallurgy iron-based parts after diffusion heat treatment in a method for improving the tensile properties of powder metallurgy iron-based parts according to Embodiment 1 of the present invention.
[0035] Figure 3 This is an XRD pattern of the boronized layer in a method for improving the tensile properties of powder metallurgy iron-based parts according to Embodiment 1 of the present invention; wherein, 900-8B-1000-6DA is boronized by holding at 900℃ for 8h, air cooling, and then diffusion homogenization treatment at 1000℃ for 6h; 900-4B-1000-6DA is boronized by holding at 900℃ for 4h, air cooling, and then diffusion homogenization treatment at 1000℃ for 6h; 900-8B-1000-4DA is boronized by holding at 900℃ for 8h, air cooling, and then diffusion homogenization treatment at 1000℃ for 4h; (a) is the overall XRD phase analysis diagram of the three markings, and (b) is a magnified view of a part in (a).
[0036] Figure 4 This is a hardness distribution curve from the surface to the interior of the boronizing layer in a method for improving the tensile properties of powder metallurgy iron-based parts according to Embodiment 1 of the present invention.
[0037] Figure 5 This is a tensile mechanical properties curve of the material prepared in the preparation method of powder metallurgy iron-based parts to improve tensile properties according to Embodiment 1 of the present invention; wherein, PM is the room temperature tensile properties of the original sample, 900-4B is the sample treated with boronizing at 900℃ for 4h, 900-6B is the sample treated with boronizing at 900℃ for 6h, 900-8B is the sample treated with boronizing at 900℃ for 8h, 900-4B-1000-4DA is the sample treated with boronizing and then diffusion annealed at 1000℃ for 4h, 900-6B-1000-4DA is the sample treated with boronizing and then diffusion annealed at 1000℃ for 6h, and 900-8B-1000-4DA is the sample treated with boronizing and then diffusion annealed at 1000℃ for 8h. Detailed Implementation
[0038] The technical solution of the present invention will now be described with reference to the accompanying drawings.
[0039] In embodiments of the present invention, words such as "exemplarily," "for example," etc., are used to indicate that something is an example, illustration, or description. Any embodiment or design described as "exemplary" in the present invention should not be construed as being more preferred or advantageous than other embodiments or designs. Specifically, the use of the word "exemplary" is intended to present the concept in a concrete manner. Furthermore, in embodiments of the present invention, the meaning expressed by "and / or" can be both, or either one.
[0040] In the embodiments of the present invention, the terms "image" and "picture" may sometimes be used interchangeably. It should be noted that when the distinction is not emphasized, their intended meanings are consistent.
[0041] In this embodiment of the invention, sometimes a subscript such as W1 may be written in a non-subscript form such as W1. When the difference is not emphasized, the meaning they express is the same.
[0042] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.
[0043] A method for preparing powder metallurgy iron-based parts with improved tensile properties, comprising the following steps:
[0044] S1. Sample processing: Clean the oil stains on the surface of the powder metallurgy iron-based parts sample, and grind and polish the sample surface to obtain a smooth iron-based parts sample.
[0045] S2, Initial powder coating of sample surface: B powder is applied to the smooth iron-based part sample surface of S1, and tantalum foil is used to wrap and compact it to obtain iron-based part sample coated with B powder.
[0046] S3. Preparation of boron-impregnated layer on sample surface: The iron-based part sample coated with B powder in S2 is placed in a tube furnace, hydrogen gas is introduced to prevent oxidation, and the sample is heated and kept at a constant temperature to obtain an iron-based part sample with a boron-impregnated layer on the surface.
[0047] S4. Diffusion treatment of samples: The iron-based parts sample with surface boronizing layer in S3 is cleaned to remove the remaining boron powder, and then subjected to diffusion heat treatment, followed by air cooling to room temperature to obtain powder metallurgy iron-based parts with improved tensile properties.
[0048] Specifically, the alloy composition of the powder metallurgy iron-based parts sample in S1 is C≤0.81wt.%, Cu≤2.07wt.%, Ni≤2.44wt.%, Mo≤0.53wt.%, Mn≤0.17wt.%, P≤0.45wt.%, with the remainder being Fe.
[0049] Specifically, the surface roughness Ra of the smooth iron-based parts sample in S1 is 0.8-2 μm.
[0050] Specifically, the B powder in S2 is an industrial B powder with a thickness of 1-3μm, which completely coats the powder metallurgy parts. The thickness of the B powder is about 3-5mm, the thickness of the tantalum foil is 0.10±0.05mm, and the pressure is 200MPa.
[0051] Specifically, the heating rate in S3 is 5-10℃ / min, the temperature is 850-950℃, the holding time is 4-8h, and the thickness of the boronized layer on the surface is 30-160μm.
[0052] Specifically, the surface hardness of the iron-based parts samples with a boron-diffused surface layer in S3 is 1440-1600 HV. 0.5 The surface porosity is 5%-20%, the surface roughness is 0.8-3.0μm, the yield strength is 265-300MPa, the tensile strength is 265-380MPa, the elongation is 2.3-4.5%, and the strength-ductility product is 0.61-1.71GPa·.
[0053] In particular, in the iron-based part sample with a surface boronizing layer in S3, the Fe2B in the surface boronizing layer has a serrated shape, a thickness of about 15-60 μm, and is distributed in the subsurface layer, growing closely with the substrate.
[0054] Specifically, in S4, the heating rate of the diffusion heat treatment is 5℃ / min, the temperature is heated to 950-1000℃, the holding time is 2-4h, and the thickness of the boronized layer on the surface is 60-95μm.
[0055] Specifically, the surface hardness of powder metallurgy iron-based parts with improved tensile properties in S4 is 1182-1230 HV. 0.5The surface porosity is 5%-10%, the surface roughness is 0.8-2.0μm, the yield strength is 100-130.3MPa, the tensile strength is 150-220.9MPa, the yield-to-tensile ratio is 0.452-0.869, the elongation is 7.8-12.4%, and the strength-ductility product is 1.17-2.74GPa·s.
[0056] In particular, in the boronized layer on the surface of powder metallurgy iron-based parts in S4 that improves tensile properties, the Fe2B has a serrated shape, a thickness of about 40-70 μm, and is relatively uniformly distributed on the surface.
[0057] In the following examples, the hardness of the prepared powder metallurgy iron-based parts was measured using an MHV-1000Z / V3.0 fully automatic micro Vickers hardness tester with a test force of HV-0.5 and a holding pressure of 10s.
[0058] The room temperature tensile test was conducted according to GB / T228.1-2021. The standard tensile specimen was dog bone shaped with a gauge length of 15 mm, a diameter of 2.5 mm, and a total length of 40 mm. The room temperature tensile test was conducted on a GNT300 electronic universal testing machine equipped with an extensometer at a tensile rate of 0.5 mm / min.
[0059] Example 1
[0060] A method for preparing powder metallurgy iron-based parts with improved tensile properties, comprising the following steps:
[0061] S1. Sample preparation: The alloy composition of the powder metallurgy iron-based parts sample is C 0.71wt.%, with the remainder being Fe; clean the oil stains on the surface of the powder metallurgy iron-based parts sample, and grind and polish the sample surface to obtain a smooth iron-based parts sample; the surface roughness Ra of the smooth iron-based parts sample is ≤2μm.
[0062] S2. Initial powder coating of sample surface: 1-3μm industrial pure B powder is used to coat the smooth iron-based part sample surface of S1, with a B powder coating thickness of about 3-5mm; it is then wrapped and compacted with tantalum foil with a thickness of 0.10mm and a compaction pressure of 200MPa; thus, the iron-based part sample coated with B powder is obtained.
[0063] S3. Preparation of boron-impregnated layer on sample surface: The iron-based part sample coated with B powder in S2 is placed in a tube furnace, hydrogen is introduced to prevent oxidation, and the sample is heated and held at a temperature of 5℃ / min. The temperature is heated to 900℃ and held for 4 hours to obtain an iron-based part sample with a boron-impregnated layer on the surface. Figure 1The dark gray layer near the top is FeB, which is also serrated. The light gray layer below, which is in contact with the substrate, is Fe2B, which is also serrated. The thickness of the boronized layer on the surface is 30±8μm.
[0064] The surface hardness of the iron-based part sample with a boron-dipped surface layer is 1440±5HV. 0.5 The surface porosity is approximately 8%, the surface roughness is 1.5 μm, the yield strength is 275 MPa, the tensile strength is 375 MPa, the yield-to-tensile ratio is 0.734, the elongation is 3.0%, and the strength-ductility product is 1.13 GPa%.
[0065] In the surface boronized layer of the iron-based part sample with surface boronized layer, Fe2B is distributed in a serrated pattern and is tightly bonded to the substrate, with a thickness of about 15±3μm.
[0066] S4. Diffusion treatment of samples: The iron-based parts sample with surface boronizing layer in S3 was cleaned to remove the remaining boron powder, and then diffusion heat treatment was performed. The heating rate of diffusion heat treatment was 5℃ / min, the temperature was heated to 900℃, the holding time was 4h, and then air-cooled to room temperature to obtain powder metallurgy iron-based parts with improved tensile properties. The thickness of the surface boronizing layer was 61.4±6μm.
[0067] Figure 2 As can be seen, after the diffusion homogenization treatment, FeB was completely dissolved to obtain a uniform Fe2B phase. The light gray area is all Fe2B. The outermost layer contains some boride particles that have not been cleaned and can be regarded as foreign objects or dirt in this field of view, rather than phase structures.
[0068] Figure 3 The XRD patterns show that 900-8B-1000-4DA underwent boronizing treatment at 900℃ for 8 hours, followed by air cooling and then diffusion homogenization treatment at 1000℃ for 4 hours. 900-4B-1000-6DA underwent boronizing treatment at 900℃ for 4 hours, followed by air cooling and then diffusion homogenization treatment at 1000℃ for 6 hours. 900-8B-1000-6DA underwent boronizing treatment at 900℃ for 8 hours, followed by air cooling and then diffusion homogenization treatment at 1000℃ for 6 hours. The overall XRD phase analysis diagrams and magnified views on the right are shown for all three. It can be seen that the boronized layer of 900-8B-1000-4DA is the Fe2B phase. Therefore, for the boronized sample treated at 900℃ for 8 hours, the optimal diffusion conditions are 1000℃ for 4 hours, which precisely achieves a complete Fe2B phase.
[0069] Figure 4 This is a Vickers hardness distribution map from the surface to the center. Figure 4 It can be seen that the hardness gradually decreases with increasing depth; when the depth reaches 50μm, the hardness is 587HV. 0.5When a depth of 100μm is reached, the hardness is 488HV. 0.5 When a depth of 150μm is reached, the hardness is 460HV. 0.5 When a depth of 200μm is reached, the hardness is 350HV. 0.5 ;
[0070] The powder metallurgy iron-based parts prepared in this embodiment, which exhibit improved tensile properties, have a surface hardness of 1440±5 HV. 0.5 The surface porosity is ≤8%, the surface roughness Ra is ≤1.5μm, the yield strength is 133.1MPa, the tensile strength is 194.8MPa, the yield-to-tensile ratio is 0.683, the elongation is 12.40%, and the strength-ductility product is 2.416GPa·.
[0071] from Figure 5 It can be seen that the room temperature tensile properties of the original sample are a yield strength of 148.3±2MPa, a tensile strength of 194.7±2MPa, and an elongation of 0.32±0.10%.
[0072] After boronizing at 900℃ for 8 hours, the yield strength increased to 288.8±2MPa, the tensile strength to 376.9±2MPa, and the elongation to 3.89±0.15%.
[0073] After boronizing at 900℃ for 6 hours and then diffusion at 1000℃ for 4 hours, the yield strength is 133.1±2MPa, the tensile strength is 194.27±2MPa, and the elongation is 9.20±0.15%.
[0074] After boronizing for 900-4 hours, diffusion was carried out at 1000℃ for 4 hours. The elongation increased from 0.32%±0.10% to 12.4±0.10%, showing a significant increase in elongation. However, the tensile strength decreased slightly to 165.7±2MPa.
[0075] In the boronized layer on the surface of the powder metallurgy iron-based part prepared in this embodiment, which improves tensile properties, Fe2B is embedded in the matrix in a serrated shape, with a thickness of about 50 μm and a relatively neat and uniform distribution.
[0076] Example 2
[0077] A method for preparing powder metallurgy iron-based parts with improved tensile properties, comprising the following steps:
[0078] S1. Sample processing: The alloy composition of the powder metallurgy iron-based parts sample is C 0.71wt.%, Cu 2.0wt.%, with the remainder being Fe; clean the oil stains on the surface of the powder metallurgy iron-based parts sample, and grind and polish the sample surface to obtain a smooth iron-based parts sample; the surface roughness Ra of the smooth iron-based parts sample is ≤2μm.
[0079] S2. Initial powder coating of sample surface: 1-3μm industrial pure B powder is used to coat the smooth iron-based part sample surface of S1, with a B powder coating thickness of about 3-5mm; it is then wrapped and compacted with tantalum foil with a thickness of 0.10mm and a compaction pressure of 200MPa; thus, the iron-based part sample coated with B powder is obtained.
[0080] S3. Preparation of boron-impregnated layer on sample surface: The iron-based part sample coated with B powder in S2 was placed in a tube furnace, hydrogen gas was introduced to prevent oxidation, and the sample was heated and held at a temperature of 5℃ / min. The temperature was raised to 900℃ and held for 4h to obtain an iron-based part sample with a boron-impregnated layer on the surface. The thickness of the boron-impregnated layer was 30±8μm.
[0081] The surface hardness of the iron-based part sample with a boron-dipped surface layer is 1440±5HV. 0.5 The surface porosity is approximately 8%, the surface roughness is 1.5 μm, the yield strength is 275 MPa, the tensile strength is 375 MPa, the yield-to-tensile ratio is 0.734, the elongation is 3.0%, and the strength-ductility product is 1.13 GPa·%.
[0082] In the surface boronized layer of the iron-based part sample with surface boronized layer, Fe2B is distributed in a serrated pattern and is tightly bonded to the substrate, with a thickness of about 15±3μm.
[0083] S4. Diffusion treatment of samples: The iron-based parts sample with surface boronizing layer in S3 was cleaned to remove the remaining boron powder, and then diffusion heat treatment was performed. The heating rate of diffusion heat treatment was 5℃ / min, the temperature was heated to 950℃, the holding time was 4h, and then air-cooled to room temperature to obtain powder metallurgy iron-based parts with improved tensile properties. The thickness of the surface boronizing layer was 65.4±6μm.
[0084] The powder metallurgy iron-based part with improved tensile properties prepared in this embodiment has a surface hardness of 1250±5HV. 0.5 The surface porosity is ≤8%, the surface roughness Ra is ≤1.5μm, the yield strength is 146.1MPa, the tensile strength is 204.8MPa, the yield-to-tensile ratio is 0.713, the elongation is 8.8%, and the strength-ductility product is 1.802GPa·.
[0085] In the boronizing layer on the surface of the powder metallurgy iron-based part prepared in this embodiment, which improves tensile properties, Fe2B is embedded in the matrix in a serrated shape, with a thickness of about 60 μm and a relatively neat and uniform distribution.
[0086] Example 3
[0087] A method for preparing powder metallurgy iron-based parts with improved tensile properties, comprising the following steps:
[0088] S1. Sample preparation: The alloy composition of the powder metallurgy iron-based parts sample is C 0.50wt.%, Cu 1.50wt.%, Ni 1.75wt.%, Mo 0.50wt.%, Mn 0.13wt.%, with the remainder being Fe. The oil stains on the surface of the powder metallurgy iron-based parts sample are cleaned, and the sample surface is ground and polished to obtain a smooth iron-based parts sample. The surface roughness Ra of the smooth iron-based parts sample is ≤2μm.
[0089] S2. Initial powder coating of sample surface: 1-3μm industrial pure B powder is used to coat the smooth iron-based part sample surface of S1, with a B powder coating thickness of about 3-5mm; it is then wrapped and compacted with tantalum foil with a thickness of 0.10mm and a compaction pressure of 200MPa; thus, the iron-based part sample coated with B powder is obtained.
[0090] S3. Preparation of boron-impregnated layer on sample surface: The iron-based part sample coated with B powder in S2 was placed in a tube furnace, hydrogen gas was introduced to prevent oxidation, and the sample was heated and held at a temperature of 5℃ / min. The temperature was raised to 900℃ and held for 4h to obtain an iron-based part sample with a boron-impregnated layer on the surface. The thickness of the boron-impregnated layer was 30±8μm.
[0091] The surface hardness of the iron-based part sample with a boron-dipped surface layer is 1440±5HV. 0.5 The surface porosity is approximately 8%, the surface roughness is 1.5 μm, the yield strength is 275 MPa, the tensile strength is 375 MPa, the yield-to-tensile ratio is 0.734, the elongation is 3.0%, and the strength-ductility product is 1.13 GPa·%.
[0092] In the surface boronized layer of the iron-based part sample with surface boronized layer, Fe2B is distributed in a serrated shape and is tightly bonded to the substrate, with a thickness of about 15±3μm.
[0093] S4. Diffusion treatment of samples: The iron-based parts sample with surface boronizing layer in S3 was cleaned to remove the remaining boron powder, and then diffusion heat treatment was performed. The heating rate of diffusion heat treatment was 5℃ / min, the temperature was heated to 900℃, the holding time was 6h, and then air-cooled to room temperature to obtain powder metallurgy iron-based parts with improved tensile properties. The thickness of the surface boronizing layer was 60.2±2μm.
[0094] The surface hardness of the powder metallurgy iron-based part with improved tensile properties prepared in this embodiment is 1182±8HV. 0.5 The surface porosity is ≤8%, the surface roughness Ra is ≤1.5μm, the yield strength is 165.5MPa, the tensile strength is 188.8MPa, the yield-to-tensile ratio is 0.877, the elongation is 9.90%, and the strength-ductility product is 1.869GPa·.
[0095] In the boronizing layer on the surface of the powder metallurgy iron-based part prepared in this embodiment, which improves tensile properties, Fe2B is embedded in the matrix in a serrated shape, with a thickness of about 68 μm and a relatively neat and uniform distribution.
[0096] Example 4
[0097] A method for preparing powder metallurgy iron-based parts with improved tensile properties, comprising the following steps:
[0098] S1. Sample preparation: The alloy composition of the powder metallurgy iron-based parts sample is C 0.73wt.%, Cu 2.07wt.%, Ni 1.75wt.%, Mo 0.53wt.%, Mn 0.17wt.%, with the remainder being Fe. The oil stains on the surface of the powder metallurgy iron-based parts sample were cleaned, and the sample surface was ground and polished to obtain a smooth iron-based parts sample. The surface roughness Ra of the smooth iron-based parts sample is ≤2μm.
[0099] S2. Initial powder coating of sample surface: 1-3μm industrial pure B powder is used to coat the smooth iron-based part sample surface of S1, with a B powder coating thickness of about 3-5mm; it is then wrapped and compacted with tantalum foil with a thickness of 0.10mm and a compaction pressure of 200MPa; thus, the iron-based part sample coated with B powder is obtained.
[0100] S3. Preparation of boron-impregnated layer on sample surface: The iron-based part sample coated with B powder in S2 was placed in a tube furnace, hydrogen gas was introduced to prevent oxidation, and the sample was heated and held at a temperature of 5℃ / min. The temperature was raised to 900℃ and held for 8h to obtain an iron-based part sample with a boron-impregnated layer on the surface. The thickness of the boron-impregnated layer was 30±8μm.
[0101] The surface hardness of the iron-based part sample with a boron-dipped surface layer is 1580±5HV. 0.5 The surface porosity is approximately 8%, the roughness is ≤1.5μm, the yield strength is 275MPa, the tensile strength is 375MPa, the yield-to-tensile ratio is 0.73, the elongation is 4.0%, and the strength-ductility product is 1.5GPa·%.
[0102] In the surface boronized layer of the iron-based part sample with surface boronized layer, Fe2B is distributed in a serrated pattern and is tightly bonded to the substrate, with a thickness of about 15±3μm.
[0103] S4. Diffusion treatment of samples: The iron-based parts sample with surface boronizing layer in S3 was cleaned to remove the remaining boron powder, and then diffusion heat treatment was performed. The heating rate of diffusion heat treatment was 5℃ / min, the temperature was heated to 1000℃, the holding time was 4h, and then air-cooled to room temperature to obtain powder metallurgy iron-based parts with improved tensile properties. The thickness of the surface boronizing layer was 73.5±6μm.
[0104] The surface hardness of the powder metallurgy iron-based part with improved tensile properties prepared in this embodiment is 1182±8HV. 0.5 The surface porosity is ≤8%, the surface roughness Ra is ≤1.5μm, the yield strength is 120.3MPa, the tensile strength is 155.4MPa, the yield-to-tensile ratio is 0.774, the elongation is 8.05%, and the strength-ductility product is 1.251GPa·.
[0105] In the boronized layer on the surface of the powder metallurgy iron-based part prepared in this embodiment, which improves tensile properties, Fe2B is embedded in the matrix in a serrated shape, with a thickness of about 50 μm and a relatively neat and uniform distribution.
[0106] Example 5
[0107] A method for preparing powder metallurgy iron-based parts with improved tensile properties, comprising the following steps:
[0108] S1. Sample preparation: The alloy composition of the powder metallurgy iron-based parts sample is C 0.72wt.%, Cu 0.98wt.%, Ni 2.44wt.%, with the remainder being Fe. The oil stains on the surface of the powder metallurgy iron-based parts sample are cleaned, and the sample surface is ground and polished to obtain a smooth iron-based parts sample. The surface roughness Ra of the smooth iron-based parts sample is ≤2μm.
[0109] S2. Initial powder coating of sample surface: 1-3μm industrial pure B powder is used to coat the smooth iron-based part sample surface of S1, with a B powder coating thickness of about 3-5mm; it is then wrapped and compacted with tantalum foil with a thickness of 0.10mm and a compaction pressure of 200MPa; thus, the iron-based part sample coated with B powder is obtained.
[0110] S3. Preparation of boron-impregnated layer on sample surface: The iron-based part sample coated with B powder in S2 was placed in a tube furnace, hydrogen gas was introduced to prevent oxidation, and the sample was heated and held at a temperature of 5℃ / min. The temperature was raised to 900℃ and held for 8h to obtain an iron-based part sample with a boron-impregnated layer on the surface. The thickness of the boron-impregnated layer was 30±8μm.
[0111] The surface hardness of the iron-based part sample with a boron-dipped surface layer is 1580±5HV. 0.5 The surface porosity is approximately 8%, the roughness is ≤1.5μm, the yield strength is 275MPa, the tensile strength is 375MPa, the yield-to-tensile ratio is 0.73, the elongation is 4.0%, and the strength-ductility product is 1.5GPa·%.
[0112] In the surface boronized layer of the iron-based part sample with surface boronized layer, Fe2B is distributed in a serrated pattern and is tightly bonded to the substrate, with a thickness of about 15±3μm.
[0113] S4. Diffusion treatment of samples: The iron-based parts sample with surface boronizing layer in S3 was cleaned to remove the remaining boron powder, and then diffusion heat treatment was performed. The heating rate of diffusion heat treatment was 5℃ / min, the temperature was heated to 1000℃, the holding time was 4h, and then air-cooled to room temperature to obtain powder metallurgy iron-based parts with improved tensile properties. The thickness of the surface boronizing layer was 73.5±10μm.
[0114] The powder metallurgy iron-based part with improved tensile properties prepared in this embodiment has a surface hardness of 1220±5HV. 0.5 The surface porosity is ≤8%, the surface roughness Ra is ≤1.5μm, the yield strength is 138.1MPa, the tensile strength is 204.6MPa, the yield-to-tensile ratio is 0.675, the elongation is 9.40%, and the strength-ductility product is 1.923GPa·.
[0115] In the boronized layer on the surface of the powder metallurgy iron-based part prepared in this embodiment, which improves tensile properties, Fe2B is embedded in the matrix in a serrated shape, with a thickness of about 65 μm and a relatively neat and uniform distribution.
[0116] Example 6
[0117] A method for preparing powder metallurgy iron-based parts with improved tensile properties, comprising the following steps:
[0118] S1. Sample preparation: The alloy composition of the powder metallurgy iron-based parts sample is C 0.81wt.%, with the remainder being Fe; clean the oil stains on the surface of the powder metallurgy iron-based parts sample, and grind and polish the sample surface to obtain a smooth iron-based parts sample; the surface roughness Ra of the smooth iron-based parts sample is ≤2μm.
[0119] S2. Initial powder coating of sample surface: 1-3μm industrial pure B powder is used to coat the smooth iron-based part sample surface of S1, with a B powder coating thickness of about 3-5mm; it is then wrapped and compacted with tantalum foil with a thickness of 0.10mm and a compaction pressure of 200MPa; thus, the iron-based part sample coated with B powder is obtained.
[0120] S3. Preparation of boron-impregnated layer on sample surface: The iron-based part sample coated with B powder in S2 was placed in a tube furnace, hydrogen gas was introduced to prevent oxidation, and the sample was heated and held at a temperature of 5℃ / min. The temperature was raised to 900℃ and held for 8h to obtain an iron-based part sample with a boron-impregnated layer on the surface. The thickness of the boron-impregnated layer was 30±8μm.
[0121] The surface hardness of the iron-based part sample with a boron-dipped surface layer is 1580±5HV. 0.5 The surface porosity is approximately 8%, the roughness is ≤1.5μm, the yield strength is 275MPa, the tensile strength is 375MPa, the yield-to-tensile ratio is 0.73, the elongation is 4.0%, and the strength-ductility product is 1.5GPa·%.
[0122] In the surface boronized layer of the iron-based part sample with surface boronized layer, Fe2B is distributed in a serrated pattern and is tightly bonded to the substrate, with a thickness of about 15±3μm.
[0123] S4. Diffusion treatment of samples: The iron-based parts sample with surface boronizing layer in S3 was cleaned to remove the remaining boron powder, and then diffusion heat treatment was performed. The heating rate of diffusion heat treatment was 5℃ / min, the temperature was heated to 1000℃, the holding time was 4h, and then air-cooled to room temperature to obtain powder metallurgy iron-based parts with improved tensile properties. The thickness of the surface boronizing layer was 72.6±4μm.
[0124] The powder metallurgy iron-based part with improved tensile properties prepared in this embodiment has a surface hardness of 1230 HV. 0.5 The surface porosity is ≤8%, the surface roughness Ra is ≤1.5μm, the yield strength is 138.1MPa, the tensile strength is 165.7MPa, the yield-to-tensile ratio is 0.833, the elongation is 10.20%, and the strength-ductility product is 1.690GPa·.
[0125] In the boronized layer on the surface of the powder metallurgy iron-based part prepared in this embodiment, which improves tensile properties, Fe2B is embedded in the matrix in a serrated shape, with a thickness of about 50 μm and a relatively neat and uniform distribution.
[0126] Example 7
[0127] A method for preparing powder metallurgy iron-based parts with improved tensile properties, comprising the following steps:
[0128] S1. Sample processing: The alloy composition of the powder metallurgy iron-based parts sample is C 0.73wt.%, Cu 2.01wt.%, Mo 0.45wt.%, with the remainder being Fe; clean the oil stains on the surface of the powder metallurgy iron-based parts sample, and grind and polish the sample surface to obtain a smooth iron-based parts sample; the surface roughness Ra of the smooth iron-based parts sample is ≤2μm;
[0129] S2. Initial powder coating of sample surface: 1-3μm industrial pure B powder is used to coat the smooth iron-based part sample surface of S1, with a B powder coating thickness of about 3-5mm; it is then wrapped and compacted with tantalum foil with a thickness of 0.10mm and a compaction pressure of 200MPa; thus, the iron-based part sample coated with B powder is obtained.
[0130] S3. Preparation of boron-impregnated layer on sample surface: The iron-based part sample coated with B powder in S2 was placed in a tube furnace, hydrogen gas was introduced to prevent oxidation, and the sample was heated and held at a temperature of 5℃ / min. The temperature was raised to 900℃ and held for 8h to obtain an iron-based part sample with a boron-impregnated layer on the surface. The thickness of the boron-impregnated layer was 30±8μm.
[0131] The surface hardness of the iron-based part sample with a boron-dipped surface layer is 1580±5HV. 0.5 The surface porosity is approximately 8%, the roughness is ≤1.5μm, the yield strength is 275MPa, the tensile strength is 375MPa, the yield-to-tensile ratio is 0.73, the elongation is 4.0%, and the strength-ductility product is 1.5GPa·%.
[0132] In the surface boronized layer of the iron-based part sample with surface boronized layer, Fe2B is distributed in a serrated pattern and is tightly bonded to the substrate, with a thickness of about 15±3μm.
[0133] S4. Diffusion treatment of samples: The iron-based parts sample with surface boronizing layer in S3 was cleaned to remove the remaining boron powder, and then diffusion heat treatment was performed. The heating rate of diffusion heat treatment was 5℃ / min, the temperature was heated to 1000℃, the holding time was 6h, and then air-cooled to room temperature to obtain powder metallurgy iron-based parts with improved tensile properties. The thickness of the surface boronizing layer was 94.2±10μm.
[0134] The surface hardness of the powder metallurgy iron-based part with improved tensile properties prepared in this embodiment is 1158±8HV. 0.5 The surface porosity is ≤8%, the surface roughness Ra is ≤1.5μm, the yield strength is 166.0MPa, the tensile strength is 208.4MPa, the yield-to-tensile ratio is 0.797, the elongation is 10.20%, and the strength-ductility product is 2.126GPa·.
[0135] In the boronizing layer on the surface of the powder metallurgy iron-based part prepared in this embodiment, which improves tensile properties, Fe2B is embedded in the matrix in a serrated shape, with a thickness of about 45 μm and a relatively neat and uniform distribution.
[0136] The above-mentioned solution, proposed by the present invention, is a method for improving the tensile properties of powder metallurgy iron-based parts. It can solve the technical problems existing in the prior art. For example, powder metallurgy iron-based parts only focus on adding boron to improve the surface hardness and thus improve wear resistance, without paying attention to the formation of Fe2B single-phase structure and the improvement of tensile properties. Moreover, the prepared surface boron-diffused layer is either too thin or the structure is unevenly distributed, without the diffusion of the structure. Some are just a coating layer prepared on the material surface, which cannot improve the overall tensile properties of the parts.
[0137] The preparation method of this invention is simple, uses only B powder as raw material instead of composite slurry, has low production cost, and the thickness of the diffusion layer can be adjusted according to the heat preservation time and temperature, which can significantly improve the density and room temperature mechanical properties of powder metallurgy materials, and is easy to promote to other metal material fields.
[0138] This invention achieves uniform coating of B-powder on the sample surface through initial powder coating, effectively avoiding the problem of uneven infiltration layer.
[0139] This invention prepares a boron-impregnated layer on the sample surface, resulting in a FeB+Fe2B double-layer boron-impregnated layer, which significantly improves yield strength, tensile strength, surface hardness, and wear resistance.
[0140] This invention improves the density of powder metallurgy materials through sample diffusion treatment, increases the proportion of Fe2B, improves plasticity, and enhances overall performance.
[0141] The surface hardness of the powder metallurgy iron-based parts with improved tensile properties prepared by this invention is 1182-1230 HV. 0.5The surface porosity is 5%-10%, the surface roughness is 0.8-2.0μm, the yield strength is 100-130.3MPa, the tensile strength is 150-220.9MPa, the yield-to-tensile ratio is 0.452-0.869, the elongation is 7.8-12.4%, and the strength-ductility product is 1.17-2.74GPa·s.
[0142] In summary, compared with other traditional methods, the method of this invention can obtain a single-layer, dense Fe2B diffusion layer with a thickness of 60-95μm in powder metallurgy low alloy steel through boronizing and diffusion heat treatment. The surface layer has few pores and no subsequent grinding processing is required, which can greatly improve hardness, strength and elongation. The method is simple to operate, environmentally friendly, low in cost, short in process and high in efficiency, which is conducive to large-scale industrial production and promotion.
[0143] It should be understood that the term "and / or" in this article is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. Additionally, the character " / " in this article generally indicates an "or" relationship between the preceding and following related objects, but it can also represent an "and / or" relationship. Please refer to the context for a more accurate understanding.
[0144] In this invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of a single item or a plurality of items. For example, at least one of a, b, or c can represent: a, b, c, ab, ac, bc, or abc, where a, b, and c can be a single item or multiple items.
[0145] It should be understood that, in various embodiments of the present invention, the order of the above-mentioned process numbers does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0146] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for preparing powder metallurgy iron-based parts with improved tensile properties, characterized in that, The preparation method for improving the tensile properties of the powder metallurgy iron-based parts is as follows: S1. Sample preparation: Clean the oil stains on the surface of the powder metallurgy iron-based parts sample, and grind and polish the sample surface to obtain a smooth iron-based parts sample; the alloy composition of the powder metallurgy iron-based parts sample is C≤0.81wt.%, Cu≤2.07wt.%, Ni≤2.44wt.%, Mo≤0.53wt.%, Mn≤0.17wt.%, P≤0.45wt.%, with the remainder being Fe; S2. Initial powder coating of the sample surface: B powder is used to cover the smooth iron-based part sample surface in S1. The B powder is 1-3μm industrial B powder. The B powder completely coats the powder metallurgy part. The B powder thickness is 3-5mm. The tantalum foil thickness is 0.10±0.05mm. The pressure is 200MPa. The tantalum foil is used to coat and compact it to obtain the iron-based part sample coated with B powder. S3. Preparation of boron-impregnated layer on sample surface: The iron-based part sample coated with B powder in S2 is placed in a tube furnace, hydrogen gas is introduced to prevent oxidation, and the sample is heated and kept at a constant temperature to obtain an iron-based part sample with a boron-impregnated layer on the surface. S4. Diffusion treatment of samples: The iron-based parts sample with surface boronizing layer in S3 is cleaned to remove the remaining boron powder, and then subjected to diffusion heat treatment, followed by air cooling to room temperature to obtain powder metallurgy iron-based parts with improved tensile properties.
2. The method for preparing powder metallurgy iron-based parts with improved tensile properties according to claim 1, characterized in that, The surface roughness Ra of the smooth iron-based parts sample in S1 is 0.8-2 μm.
3. The method for preparing powder metallurgy iron-based parts with improved tensile properties according to claim 1, characterized in that, The heating rate in S3 is 5-10℃ / min, the temperature is 850-950℃, the holding time is 4-8h, and the thickness of the boronized layer on the surface is 30-160μm.
4. The method for preparing powder metallurgy iron-based parts with improved tensile properties according to claim 1, characterized in that, The surface hardness of the iron-based parts samples with a boronized surface layer in S3 is 1440-1600 HV. 0.5 The surface porosity is 5%-20%, the surface roughness is 0.8-3.0μm, the yield strength is 265-300MPa, the tensile strength is 265-380MPa, the elongation is 2.3-4.5%, and the strength-ductility product is 0.61-1.71GPa·.
5. The method for preparing powder metallurgy iron-based parts with improved tensile properties according to claim 1, characterized in that, In the S3 sample of iron-based parts with a surface boronizing layer, the Fe2B in the surface boronizing layer is serrated, with a thickness of 15-60 μm, distributed in the subsurface layer, and grows tightly with the substrate.
6. The method for preparing powder metallurgy iron-based parts with improved tensile properties according to claim 1, characterized in that, The heating rate of diffusion heat treatment in S4 is 5℃ / min, the temperature is 950-1000℃, the holding time is 2-4h, and the thickness of the boronized layer on the surface is 60-95μm.
7. The method for preparing powder metallurgy iron-based parts with improved tensile properties according to claim 1, characterized in that, The surface hardness of powder metallurgy iron-based parts with improved tensile properties in S4 is 1182-1230 HV. 0.5 The surface porosity is 5%-10%, the surface roughness is 0.8-2.0μm, the yield strength is 100-130.3MPa, the tensile strength is 150-220.9MPa, the yield-to-tensile ratio is 0.452-0.869, the elongation is 7.8-12.4%, and the strength-ductility product is 1.17-2.74GPa·s.
8. The method for preparing powder metallurgy iron-based parts with improved tensile properties according to claim 1, characterized in that, In the boronizing layer on the surface of powder metallurgy iron-based parts in S4 that improves tensile properties, Fe2B has a serrated shape, a thickness of 40-70μm, and is relatively uniformly distributed on the surface.
Citation Information
Patent Citations
Metal surface boronisation superhard treatment process
CN108796426A
Boriding method capable of improving wear resistance of steel and iron surfaces
CN109487314A
Preparation method of boron particle reinforced metal matrix composite material, composite material and application of composite material
CN113481503A